EFFECT OF SOCIOECONOMIC BACKGROUND ON DRUG ADDICTION AMONG PATIENTS IN KARU GENERAL HOSPITAL ABUJA - OMOZUSI MERCY OMOSEFE; SHALWUL MONICA MIDONG; AZORONDU AGBONS ABIGAIL (International Studies Journal)
The rate of drug addiction has been increasing overtime and it could be traced to some social and economic issues. There is not much study on these issues in relation to drug addiction thus this study was designed to examine the effect of socioeconomic background on drug addiction among patients in Karu general hospital, Abuja. Nigeria. This study employed a quantitative cross-sectional survey research design with a sample size of 82 patients. Data was analyzed using simple percentage, mean and standard deviation score method with result of the data at 0.05 level of significance. Findings revealed that there was a significant relationship between social background and drug addiction (r= 0.407, P< 0.05), there was also a significant relationship between economic background and drug addiction (r= 0.489, P< 0.05). The study concludes that social background and economic background has effect on drug addiction. Some of the recommendations werecommunity members should participate and get involve in identifying drug abusers and the sellers of such drugs and report to appropriate authority for prompt action; government should work out policies and modalities that will improve the overall economic status of Nigerians and lastly parents should work harder to provide the basic needs of their families.